Manganese in Diagnostics: A Preformulatory Study - Maddalena Sguizzato; Walter Pula; Anna Bordin; Antonella Pagnoni; Markus Drechsler; Lorenza Marvelli; Rita Cortesi (MDPI AG, 2022)
This investigation aims to find lipid-based nanosystems to be used as tools to deliver manganese for diagnostic purposes in multimodal imaging techniques. In particular, the study describes the production and characterization of aqueous dispersions of anionic liposomes as delivery systems for two model manganese-based compounds, namely manganese chloride and manganese acetylacetonate. Negatively charged liposomes were obtained using four different anionic surfactants, namely sodium docusate (SD), N-lauroylsarcosine (NLS), Protelan AG8 (PAG) and sodium lauroyl lactylate (SLL). Liposomes were produced by the direct hydration method followed by extrusion and characterized in terms of size, polydispersity, surface charge and stability over time. After extrusion, liposomes are homogeneous and monodispersed with an average diameter not exceeding 200 nm and a negative surface charge as confirmed by ζ potential measurement. Moreover, as indicated by atomic absorption spectroscopy analyses, the loading of manganese-based compounds was almost quantitative. Liposomes containing NLS or SLL were the most stable over time and the presence of manganese-based compounds did not affect their size distribution. Liposomes containing PAG and SD were instable and therefore discarded. The in vitro cytotoxicity of the selected anionic liposomes was evaluated by MTT assay on human keratinocyte. The obtained results highlighted that the toxicity of the formulations is dose dependent.